The effect of resveratrol on sphingosine-1 and oxidative/ nitrosative stress in an experimental heart ischemia reperfusion model - Avnioğlu, Seda; Güngör, Meltem; Kurutaş, Ergül; Öztürk, Ünal; Demirhan, İlter; Bakariş, Sevgi; Velioğlu, Halil Aziz; Çankaya, Şeyda; Yuluğ, Burak (University Press, 2022)
Objectives: Resveratrol (RSV) is a natural polyphenolic compound showing significant antioxidant effects. In this study, we aimed to investigate the effects of resveratrol on the sphingosine-1-phosphate (S1P) and oxidative stress biomarkers in hearth ischemia-reperfusion (I/R). Materials and Methods: The biochemical and histopathological effects of RSV on cardiac ischemia-reperfusion injury were investigated through ELISA- and light microscope. Results: We observed statistically significant differences between the treatment group and the control group in terms of malondialdehyde (MDA) level, catalase (CAT) and superoxide dismutase (SOD) activities (p<0.05). Histopathologically, we also observed decreased Polymorphonuclear Leucocyte (PMNL) infiltration, myocardial edema, miyositolysis in the treatment group compared to the I/R and sham groups. Conclusion: Resveratrol may play an important role in cardiac I/R injury through its anti-inflammatory and antioxidant effects which were biochemically and histopathologically confirmed in the present study.
Keywords: Resveratrol; Ischemia/Reperfusion Injury; Antioxidant; Oxidative Stress; Heart